Spouses with benefits: On match quality and consumption inside households - Martin James Browning; Laurens Cherchye; Thomas Demuynck; Bram de Rock; Frederic Vermeulen (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2024)
We model the interaction between the marriage market and the intrahousehold allocation of resources. We do this within a setting that accounts for both economic gains to marriage (through public consumption) and unobserved non-material match quality, without relying on the transferable utility assumption. We adopt an axiomatic approach that leads to the empirically tractable "Additive Quantity Shifting" (AQS) model. We develop a revealed preference methodology that is able to identify individuals' heterogeneous match qualities and to quantify them in money metric terms. The methodology can include both preference factors, affecting individuals' preferences over private and public goods, and match quality factors, driving differences in unobserved match quality. We demonstrate the practical usefulness of our methodology through an application to the Belgian MEqIn data. Our results reveal intuitive patterns of match quality that allow us to rationalise both the observed matches and the within-household allocations of time and money.
Keywords: C14; D11; C78; 330; household consumption; marital stability; unobserved match quality; revealed preference analysis; intrahousehold allocation